Earth Construction: Ancestral Techniques for Current Problems - Cuitiño Rosales, Maria Guadalupe (2019)
It is undeniable that earth architecture is found in all the regions and civilizations of the world, Fig. 1, strongly rooted in the culture of each town and popular knowledge of each region, being evidence of this the city of Jericho (Israel), the Village Katal Hüyuk (Turkey), the citadels of the Chimú culture in Chan Chan (Peru), the reinforced earth wall of Joya de Cerén (El Salvador), and different archaeological findings in Africa, Asia, Europe and America. It is a technology that is still used today, and due to technological knowledge, it has been possible to improve the different techniques that involve earth as a raw material. In many localities the housing situation is really critical, due to a housing deficit or the structural deterioration of precarious housing, which risk the lives of those people who inhabit those constructions. There are cases in which the use of alternative construction techniques is a solution to this problem, so it is resorted to buildings where clay soils, sand and straw are the main components in this construction types.